The Berenstain Bear Scouts and the magic crystal caper - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012.; Berenstain, Mike, 1951- (New York : Scholastic, 1997)
The Bear Scouts help Grizzly Gran find her missing magic crystal ball.
"A Little Apple paperback."
2.
007-010.
Keywords: Scouting (Reconnaissance) -- Fiction; Scouting (Youth activity) -- Fiction; Scouts (Reconnaissance) -- Fiction; Scouts (Youth organization members) -- Fiction; Fortune-telling -- Fiction